2018
DOI: 10.1007/978-3-319-96041-8_13
|View full text |Cite
|
Sign up to set email alerts
|

Epilogue: What’s the Matter with Rotterdam?

Abstract: What’s the matter with Rotterdam? This is a question I asked in a 2017 lecture (available to view at www.mmg.mpg.de), when trying to figure out how and why the city seems to disrupt common contemporary narratives concerning migration and cities. That is, social scientists since Simmel have postulated that cities are largely incubators of cosmopolitanism, or openness (if only indifference) to socio-cultural differences. It is often presumed that such openness goes together with an acceptance of ethnic diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…According to academics and city officials alike, Rotterdam turned 'superdiverse' in the mid-2010s, when official statistics showed that more than half of its population were migrants or children of migrant parents. Some see Rotterdam today as a 'majority minority city', where 'no one is in the majority' (Crul et al, 2019;Vertovec, 2019). It is a city where the number of migrant groups has increased; groups themselves have diversified internally; and differences related to religion, gender, sexuality, and generation have further increased the complexities of urban diversity (Scholten et al, 2019).…”
Section: The Case Of Rotterdammentioning
confidence: 99%
“…According to academics and city officials alike, Rotterdam turned 'superdiverse' in the mid-2010s, when official statistics showed that more than half of its population were migrants or children of migrant parents. Some see Rotterdam today as a 'majority minority city', where 'no one is in the majority' (Crul et al, 2019;Vertovec, 2019). It is a city where the number of migrant groups has increased; groups themselves have diversified internally; and differences related to religion, gender, sexuality, and generation have further increased the complexities of urban diversity (Scholten et al, 2019).…”
Section: The Case Of Rotterdammentioning
confidence: 99%